The Effectiveness of Problem‐Based Learning in Reducing Work‐Related Musculoskeletal Problems Among Hospital Nurses: An Interventional Study: Problem‐Based Learning and Nurses' Musculoskeletal Problems. - Modarresi, Shahrzad; Rakhshani, Tayebeh; Mehri, Zahra; Kaydani, Masoumeh; Rasouli Kahaki, Zeinab; Rahgoshay, Niloofar; Daneshmandi, Hadi; Ahmed, Sirwan Khalid (Nursing Forum, 2024)
Background: Musculoskeletal disorders (MSDs) are common among nursing professionals and require effective management strategies. Implementing targeted training programs for nurses is a vital approach to reduce these problems. Aim: This study aimed to evaluate problem‐based learning (PBL) effectiveness in reducing work‐related musculoskeletal symptoms (WMSs) among nurses. Methods: Fifty Iranian nurses participated in this interventional study. Some data were collected by a demographic/occupational questionnaire and a Persian version of the Nordic Musculoskeletal Questionnaire (P‐NMQ). Some other was gathered by Rapid Entire Body Assessment (REBA) and PBL method. Results: The prevalence of WMSs during the last 12 months in the subjects was related to the lower back (76%), wrists/hands (70%), neck (64%), and knee (64%), respectively. The results showed that the prevalence of WMSs decreased significantly only in the subjects' elbow region in the postintervention (p = 0.031). Although the prevalence decreased in the postintervention stage in other regions, this decrease was not statistically significant (p > 0.05). Conclusions: This study showed that the implementation of PBL could reduce the WMSs prevalence and the level of nurses' exposure to risk factors for MSDs.